2010
DOI: 10.1007/s13213-010-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Escherichia coli O157:H7 isolated from cattle and sheep

Abstract: A total of 102 Escherichia coli O157:H7 colonies recovered from 11 cattle and 14 sheep were collected and tested for their antibiotic resistance profiles using a disc diffusion method, according to the Clinical and Laboratory Standards Institute. Four (36.36 %) of the 11 cattle E. coli O157:H7 isolates were resistant to cephalothin, one (9.09 %) isolate was resistant to streptomycin, and one (9.09 %) to nalidixic acid. Two (14.28 %) of the 14 sheep E. coli O157:H7 isolates were resistant to sulphamethoxazole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
(22 reference statements)
7
14
0
1
Order By: Relevance
“…Most of the isolates in this study were sensitive to these antibiotics. These results are consistent with previous studies (Hiko et al 2008;Goncuoglu et al 2010). However, Abong'o and Momba (2009) found 75 % (4/5) of E. coli O157:H7 isolates from meat were resistant to gentamicin.…”
Section: Resultssupporting
confidence: 92%
“…Most of the isolates in this study were sensitive to these antibiotics. These results are consistent with previous studies (Hiko et al 2008;Goncuoglu et al 2010). However, Abong'o and Momba (2009) found 75 % (4/5) of E. coli O157:H7 isolates from meat were resistant to gentamicin.…”
Section: Resultssupporting
confidence: 92%
“…From the result of the present study, it was observed that the susceptibility of the E coli isolates were high (100%) against Amoxycillin, Ampicillin, Amoxycillinclavulanate, Norfloxacin and Pefloxacin; but with other antimicrobial agents such as Ciprofloxacin and Ofloxacin, their susceptibility was low ranging from 10 to 22% respectively. From the observations made in the present study, the susceptibility pattern of the E coli isolates is similar to what was reported by Emikpe et al (2009) in goats in southern Nigeria, but in variance with previous observations made elsewhere (Goncuoglu et al, 2010;Khan et al, 2004;Martins et al, 2009). For example, while both Goncuoglu et al, (2010) and Martins et al, (2009), showed that Ciprofloxacin was highly effective (100%) against vaginal E coli isolates, our study demonstrated low susceptibility (10%) of this pathogen to Ciprofloxacin.…”
Section: Discussionsupporting
confidence: 92%
“…From the observations made in the present study, the susceptibility pattern of the E coli isolates is similar to what was reported by Emikpe et al (2009) in goats in southern Nigeria, but in variance with previous observations made elsewhere (Goncuoglu et al, 2010;Khan et al, 2004;Martins et al, 2009). For example, while both Goncuoglu et al, (2010) and Martins et al, (2009), showed that Ciprofloxacin was highly effective (100%) against vaginal E coli isolates, our study demonstrated low susceptibility (10%) of this pathogen to Ciprofloxacin. The observation in the present study presents concern with the use of this agent in the treatment of E coli associated genital infections in ewes in this part of the world.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it was not surprising that the E. coli O157:H7 strains of our investigation had the high prevalence of resistance against ampicillin, tetracycline, gentamicin, amikacin and sulfamethoxazole antibiotics, which was covered by presence of antibiotic resistance genes. Goncuoglu et al (2010) [29] showed that prevalence of resistance of E. coli O157:H7 isolated from meat in Turkey against cephalothin, streptomycin, sulfamethoxazole and sulfonamides were 36.36%, 9.09%, 14.28% and 7.14%, respectively. Zhang et al (2015) [27] reported that E. coli O157:H7 isolates of raw meat in China were highly resistant to penicillin (100%), chloramphenicol (64.29%) and ampicillin (57.14%) which was similar to our findings.…”
Section: Discussionmentioning
confidence: 99%